2018
DOI: 10.1039/c8cp06641h
|View full text |Cite
|
Sign up to set email alerts
|

Spin state engineered ZnxCo3−xO4 as an efficient oxygen evolution electrocatalyst

Abstract: The electrocatalytic activity of ZnxCo3−xO4 for the oxygen evolution reaction is correlated with the population of high-spin Co3+ and the Co3+/Co2+ ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Spinel Co 3 O 4 is one of the most-studied OER electrocatalysts because of its high activity and relative earth-abundance of Co. Extensive efforts have been made to improve its OER activity by fabricating nanostructures to increase the surface area, , morphology control to expose more active crystal facets, , and doping to modulate its electronic structure. In the spinel structure of Co 3 O 4 , the tetrahedral ( T d ) sites are occupied by Co 2+ with e 4 t 2 3 electron configuration, whereas the octahedral ( O h ) sites are Co 3+ with t 2g 6 e g 0 electron configuration (see Figure a) . Because T d coordinated Co 2+ and O h coordinated Co 3+ exhibit different electronic properties, which site is the active site in the OER is an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Spinel Co 3 O 4 is one of the most-studied OER electrocatalysts because of its high activity and relative earth-abundance of Co. Extensive efforts have been made to improve its OER activity by fabricating nanostructures to increase the surface area, , morphology control to expose more active crystal facets, , and doping to modulate its electronic structure. In the spinel structure of Co 3 O 4 , the tetrahedral ( T d ) sites are occupied by Co 2+ with e 4 t 2 3 electron configuration, whereas the octahedral ( O h ) sites are Co 3+ with t 2g 6 e g 0 electron configuration (see Figure a) . Because T d coordinated Co 2+ and O h coordinated Co 3+ exhibit different electronic properties, which site is the active site in the OER is an open question.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the mass density of (100)‐oriented LaCoO 3 (87% IS) is 2.9 and 6.7 times higher than those of (110) and (111)‐oriented LaCoO 3 (31% IS and 48% IS). Currently, research efforts on spin states of catalysts are mainly based on the regulation of lattice planes, [ 139 ] heteroatom doping, [ 140–142 ] and material dimensions. [ 143–145 ] However, design and production of these catalysts are technically complicated.…”
Section: Magnetic Field‐assisted Electrocatalytic Her/oermentioning
confidence: 99%
“…12,13 Recent findings have revealed that, in spinel Co 3 O 4 , Co 3+ in the octahedral sites is active for the OER, 14,15 which has encouraged attempts to prepare Co 3 O 4based catalysts with Co 2+ replaced by other transition metal ions in which only Co 3+ is involved in the OER. 16,17 On the contrary, some reports have shown that Co 2+ in tetrahedral sites is active and can be easily oxidized to form CoOOH, while Co 3+ is rather inactive and may be blocked by OH groups. 18 These ongoing debates on the OER activity, particularly involving ZnCo 2 O 4 material, have yet to be resolved.…”
Section: ■ Introductionmentioning
confidence: 99%